Improving the Quality of Good Governance by Improving the Quality of Integrated Digital-Based Services in Sub-districts Throughout Indonesia: Penelitian - Bram B Baan; Rahmi Setiawati; Ika Agustina; Selvianus Salakay; Eva Desembrianita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The author conducted this socialization in several villages, namely Manusak Village, East Kupang, Rahong Village, Cianjur, West Java, and Bakalan Village, Bululawang for twenty-five days. The author conducted this socialization because of the author's anxiety because the integrated digital service system had not been implemented in Indonesia. The conclusion in this aticle that the village must have these three objects to implement a digital-based integrated public service system in the village. Young human resources are needed because the adaptation of the mini site is not short and must be applied for a long time, the website is needed because it is a symbol of the first stage of digital service reporting and the easiest to have before the village has an application. Another thing that is no less important is support from the village government to apply this system. Increasing the digital-based integrated public service system is one of the implementations of good governance in the village.